Mechanical properties of magnesium-silicon carbide composite fabricated through powder metallurgy route. (2020) - Dinesh Kumar, S.; Ravichandran, M.; Sakthivelu, S.; Meignanamoorthy, M.; Chanakyan, C.; Alagarsamy, S.V.
Abstract: In this present work, Magnesium metal matrix composites reinforced by silicon carbide were synthesized and fabricated by means of powder metallurgy process. Magnesium powder with 0, 4, 8 & 12 wt% SiC was blended in ball mill for 10 min. Then the cold compaction was done by using compression machine was compressed pressure of 650Mpa at suitable die. The sintering method was performed at 500°and 670 °C and hold time of 30 min using microwave furnace and to achieve better result to sinter the Mg metal matrix composites. The microstructure, density, compressive strength and hardness of the resultant Magnesium-Silicon carbide composites were studied. It was observed that the 12 wt% Silicon carbide reinforcements lead to the improvement in mechanical properties such as high density, high hardness, high compressive strength and high impact strength. Moreover, the outcome exposed that the density, hardness, compressive strength and impact strength of the composite was obviously higher than that of the Cast Magnesium and mechanical properties was improved with higher amount of Silicon carbide reinforcement from 0 to 12 wt%.